2019
DOI: 10.1016/j.sjbs.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Codonopis bulleynana forest ex diels on Deferribacteres in constipation predominant intestine tumor: Differential analysis

Abstract: As a complicated micro-ecosystem, gut microbes are closely related to metabolic disease, immune disease and tumor (such as constipation. Long-term constipation would cause intestinal mucosal injury, enteritis, ileus, etc., thus inducing intestine cancer). In this research, intestine cancer model group and Codonopsis foetens treatment group were successfully constructed, and the variation of intestinal microbes were analyzed by 16S rRNA sequence. Results showed that there were changes in bacteria abundance of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Deferribacteres bacteria are able to obtain energy through obligate or facultative anaerobic metabolism. The iron metabolism of Deferribacteres in intestinal flora has been shown to be related to iron balance in the gastrointestinal tract (54). By analogy, we infer that FP also may be related to iron metabolism.…”
Section: Discussionmentioning
confidence: 71%
“…Deferribacteres bacteria are able to obtain energy through obligate or facultative anaerobic metabolism. The iron metabolism of Deferribacteres in intestinal flora has been shown to be related to iron balance in the gastrointestinal tract (54). By analogy, we infer that FP also may be related to iron metabolism.…”
Section: Discussionmentioning
confidence: 71%
“…The research of Li et al. (2019) also showed that the abundance of Proteobacteria was lower in the constipation‐predominant intestine tumor group than the control group. Additionally, the Desulfovibrionales are an order of Proteobacteria , which may be the main reason for the difference of Proteobacteria levels among the groups.…”
Section: Discussionmentioning
confidence: 93%
“…In standard diet mice, the relative abundance of the phylum Deferribacteres was significantly higher after Pg administration. The phylum Deferribacteres is involved in iron metabolism, 45 and abnormal iron metabolism was F I G U R E 7 Co-occurrence network in the gut microbiome (n = 4). Co-occurrence patterns are drawn using a network structure in which each taxon and co-occurrence of genus level was indicated by a node and edge, respectively, for all taxa of genus level pairs with a positive correlation.…”
Section: Discussionmentioning
confidence: 99%